Financiamiento y cobertura prestacional del Seguro Integral de Salud en Perú, 2007 - 2023 - Quispe-Condori, Carlos Alexander (2025)
Introduction. In Peru, the creation of the Seguro Integral de Salud (SIS) represented progress toward Universal Health Coverage; however, enrollment does not guarantee access to services. Objective. To assess the correlation between SIS financing (FSIS) and service coverage (SC) in the period 2007–2023, at the national and departmental levels, and to identify factors associated with SC. Methods. We obtained annual FSIS amounts at national and departmental levels (2007–2023). Based on the National Household Survey (ENAHO), we included SIS affiliates who, in the previous four weeks, reported a health problem, sought care, and received at least one service. A patient was considered covered when at least one of these services was financed by SIS. Results. We found an inverse relationship between FSIS and the percentage of service coverage (%SC) in 2007–2023 (rho = –0.818; p<0.001). FSIS grew by an  average 23.6% annually between 2007–2015 and 5.7% between 2015–2023, while %SC decreased, with the steepest decline in 2018–2021 (–11.3% annually). The proportion of those who attended Ministry of Health (MINSA) facilities increased from 84.4% to 46.7%, but their SC decreased from 92.5% to 97.2%, whereas attendance at non-institutional providers (pharmacies and others) increased from 11.1% to 46.4% with SC rising slightly from 6.5% to 5.0%. Conclusión. Despite the sustained increase in SIS funding, service coverage decreased across most departments and sociodemographic subgroups.